Aplikasi Formulasi Media Ms Untuk Penyemaian Biji Anggrek Phalaenopsis amabilis (L.) Blume - Wahyudiningsih (Indoensia), Tri Suwarni; Rahmiyah (Indoensia), Muzayyanah; Rahmawati (Indoensia), Galuh Indah (JURNAL VIGOR, 2024)
Orchid propagation requires special media to optimize growth. The high selling price and complexity of making the media has resulted in household scale cultivators finding it difficult, so alternative media innovations have emerged that are cheaper and easier to make. The aim of this research was to analyze the effect of modified MS media formulation on the growth of moon orchid seeds (Phalaenopsis amabilis [L.] Blume). This research was carried out at the Salaman Horticultural Seed Garden Laboratory. This research used a single factor Completely Randomized Design (CRD) with 4 replications. Treatment consisted of P0 = control, P1 = MS, P2 = ½MS, P3 = Modified MS, and P4 = ½ Modified MS. The results of the research showed that the media formulation had an effect on the parameters that started to change seed color, the percentage of seeds that germinated, and the number of seeds that grew into protocorms bottle.Keywordss: in vitro culture, media formulation, orchid, phalaenopsis.